Removal of Synaptic Ca2+-Permeable AMPA Receptors during Sleep. - ULRICH, DANIEL; ROWAN, MICHAEL (My University, 2011)
here is accumulating evidence that sleep contributes to memory formation and learning, but the underlying cellular mechanisms are incompletely understood. To investigate the impact of sleep on excitatory synaptic transmission, we obtained whole-cell patch-clamp recordings from layer V pyramidal neurons in acute slices of somatosensory cortex of juvenile rats (postnatal days 21-25). In animals after the dark period, philanthotoxin 74 (PhTx)-sensitive calcium-permeable AMPA receptors (CP-AMPARs) accounted for ~25% of total EPSP size, and current-voltage (I-V) relationships of the underlying EPSCs showed inward rectification. In contrast, in similar experiments after the light period, EPSPs were PhTx insensitive with linear I-V characteristics, indicating that CP-AMPARs were less abundant. Combined EEG and EMG recordings confirmed that slow-wave sleep-associated delta wave power peaked at the onset of the more quiescent, lights-on phase of the cycle. Subsequently, we show that burst firing, a characteristic action potential discharge mode of layer V pyramidal neurons during slow-wave sleep has a dual impact on synaptic AMPA receptor composition: repetitive burst firing without synaptic stimulation eliminated CP-AMPARs by activating serine/threonine phosphatases. Additionally, repetitive burst-firing paired with EPSPs led to input-specific long-term depression (LTD), affecting Ca(2+) impermeable AMPARs via protein kinase C signaling. In agreement with two parallel mechanisms, simple bursts were ineffective after the light period but paired bursts induced robust LTD. In contrast, incremental LTD was generated by both conditioning protocols after the dark cycle. Together, our results demonstrate qualitative changes at neocortical glutamatergic synapses that can be induced by discharge patterns characteristic of non-rapid eye movement sleep.
PUBLISHED
Keywords: Neuroscience; Sleep; Memory function; Neuroscience